Paradigma Holistik Bimbingan Konseling Islam: Integrasi Dimensi Spiritual, Psikologis, dan Sosial dalam Kerangka Tauhid - Kunzita Lazuardi; Mursalim Mursalim; Siti Masrohatin (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
Islamic Guidance and Counseling (IGC) is often understood as the integration of religious values into conventional psychological practice. Such an approach tends to position spirituality as a complementary element rather than as a paradigmatic framework. This article aims to formulate a holistic paradigm of Islamic Guidance and Counseling that views human beings as an integrated unity of spiritual, psychological, and social dimensions within the framework of tawhid. This study employs a qualitative approach through library research. Data were drawn from primary sources, including the Qur’an, Hadith, and classical Islamic scholarship by figures such as Al-Ghazali and Ibn Qayyim al-Jawziyyah, as well as secondary sources consisting of nationally and internationally reputable journal articles in the fields of Islamic psychology and counseling published within the last 10–15 years. Data analysis was conducted using qualitative content analysis and textual–comparative analysis to generate a conceptual synthesis. The findings indicate that the holistic paradigm of Islamic Guidance and Counseling is structured around three core dimensions: spiritual, psychological, and social. The spiritual dimension serves as the foundational axis through the concepts of ruh, qalb, and nafs, with worship practices, aqidah, and akhlaq functioning as mechanisms of counseling intervention. The psychological dimension integrates modern psychological theories critically within an Islamic epistemological framework, positioning tawhid as a unifying metatheory. Meanwhile, the social dimension emphasizes the role of Islamic community support as an active component in the processes of healing and personal development. These findings affirm that Islamic Guidance and Counseling is not merely a religious adaptation of Western psychology, but rather a coherent scientific paradigm grounded in a comprehensive ontological and epistemological foundation. The resulting conceptual model illustrates the dynamic interrelationship among these dimensions in fostering the holistic well-being of Muslim individuals.